Disempowered by Design: Information Inequality in the Age of Inclusive Growth - A'zdom, Muhammad Khofidul; Firnanda , Deviyan Angel (Professorline, 2025)
In an era where inclusive growth has become a global development mantra, this study critically examines a frequently overlooked dimension: information inequality. While infrastructure expansion and digital inclusion are often presented as pathways to empowerment, this research argues that many development efforts are structured in ways that silence marginalized voices, particularly in peripheral regions. Using a qualitative approach combining critical discourse analysis, interviews, and case studies from remote areas in Indonesia the study explores how development communication practices reflect and reproduce power imbalances. Findings reveal that dominant narratives frame poverty as a technical issue, exclude communities from meaningful participation, and centralizing communicative control in elite institutions. At the same time, grassroots actors engage in alternative communication strategies, highlighting their agency and resilience. The study concludes that true inclusion requires not just access, but the redistribution of communicative power, enabling communities to shape the narratives and policies that define their futures. Communication, therefore, must be recognized not merely as a channel, but as a site of justice, voice, and democratic engagement in the age of inclusive growth.